The phytomass and dominant complex of benthic producers in the hydrological natural monument "Coastal aquatic complex at Cape Sarych" (the Black Sea) - Evstigneeva I.K.; Tankovskaya I.N. (Трансформация экосистем)
Phytobenthos studies in the waters of Cape Sarych suggest that Heterokontophyta is the basic producer among the divisions and Ericaria crinita, Gongolaria barbata, Vertebrata subulifera, Phyllophora crispa among the species. Indicators of benthic phytomass vary widely, being the least at great depths. By-depth changes of the cenosis phytomass and Heterokontophyta demonstrate similarity. Location of the phytomass maximum (0.5 m for Chlorophyta and 5 m for the rest) clearly indicates its dependence on light regime at the horizons and photopigment composition in species of different divisions. In terms of intra-annual dynamics, phytomass peak is noted in spring for Chlorophyta and Heterokontophyta, while for Rhodophyta and the entire phytocenosis in summer. It is characterized by strong manifestation. Long-term observations at the reference site show a threefold increase (over 20 years) in the benthic phytomass due to the Heterokontophyta development. Productional heterogeneity of the cenosis, estimated from the Shannon and Pielou indices, is lower in time than in space. By indicators of halobity and saprobity, marine and oligosaprobic species dominate by phytomass and species diversity. Brackish-water, poly- and mesosaprobic species develop en masse in sites with anthropogenic pressure.